Silent ischaemia in diabetes – does diagnosis of coronary heart disease in everyday practice happen too late? - Róg-Makal, Magdalena; Kotwa, Katarzyna; Bachórzewska-Gajewska, Hanna; Hirnle, Tomasz; Dobrzycki, Sławomir (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2008)
Diabetes mellitus is a risk factor of key importance for coronary heart disease. In diabetic patients the atherosclerotic lesions involve many vessels, are diffused and show faster progression. Also, incidences of silent ischaemia are more frequent. The course of coronary artery disease is often asymptomatic or mildly symptomatic, which makes it difficult to reach its correct diagnosis in everyday practice. This article presents a brief history of a 56-year old patient with long-standing diabetes mellitus who received treatment for heart failure and had been admitted to the hospital to undergo coronarography, because his heart failure problems were growing worse with no symptoms of angina pectoris. The echocardiography revealed enlargement of his left ventricle, low ejection fraction (EF 32%) and segmentally disordered contractibility. The coronarography indicated severe atherosclerotic lesions in many coronary vessels. This patient was treated with bypass grafts. No complications developed during surgery and surgically, he received four by after surgery and he was discharged from the hospital in a good condition. This case is an example of late-established diagnosis of coronary heart disease in diabetic patients. Therefore, such patients should be diagnosed according to guidelines of the Polish Society of Diabetology.